The Effect of styles teaching in cognitive achievement In methods of teaching physical education - Madi, Angela; Al Haj Hasan, Ameen (Latakia University Journal -Medical Sciences Series, 2018)
The research aims to identify the difference between my style and method of brainstorming Prince in the collection of knowledge of the material teaching methods. The researcher used the experimental method and the research sample consisted of students stage Cycle- Faculty of Physical Education - Tishreen University, was Achtaahm simple random way. They were divided into two groups and by 23 students for each group, one group B studied according to brainstorming and other studied Method A method according to Prince. And identified the search tool in the cognitive achievement test material teaching methods. Where the application of methods and by one lecture a week and extended the ten lectures. After the completion of the application distributed achievement test them and after data acquisition and processing means of statistical tests (t) for independent samples equal number, were obtained results and their impact on the researcher concluded the following: - Outweigh the B group that studied according to brainstorm on the members of the group A, who studied in accordance with the prescriptive method in the collection of knowledge of the material tested method of teaching methods students. The researcher recommended the need to use brainstorming method as the best method of the Prince in the material teaching methods. أثر استخدام أسلوبين تدريسيين في التحصيل المعرفي لمادة طرائق تدريس التربية البدنية يهدف البحث إلى التعرف على الفرق بين أسلوبي العصف الذهني الأمري في التحصيل المعرفي لمادة طرائق التدريس. استخدم الباحث المنهج التجريبي، وتمثلت عينة البحث بمجموعة من طلاب السنة الثالثة- كلية التربية الرياضية – جامعة تشرين، تم اختياهم بالطريقة العشوائية البسيطة, تم تقسيمهم الى مجموعتين وبواقع 23 طالباً لكل مجموعة، احداها درست وفق أسلوب العصف الذهني وسميت المجموعة B، والأخرى درست وفق الأسلوب الأمري وسميت المجموعة A. وتمثلت أداة البحث باختبار تحصيلي معرفي لمادة طرائق التدريس. تم تطبيق الأسلوبين وبواقع محاضرة واحدة في الأسبوع وممتدة على عشر محاضرات. وبعد الانتهاء من التطبيق تم تطبيق الاختبار التحصيلي عليهم وبعد الحصول على البيانات ومعالجتها بالوسائل الاحصائية المتمثلة باختبار (t) للعينات المستقلة متساوية العدد، تم الحصول على النتائج وعلى أثرها استنتج الباحث ما يأتي: - تفوق طلاب المجموعة B التي درست وفق أسلوب العصف الذهني على افراد المجموعة A التي درست وفق الأسلوب الأمري في اختبار التحصيل المعرفي لمادة طرائق التدريس. واقترح الباحث ضرورة استخدام أسلوب العصف الذهني باعتباره أفضل من الأسلوب الأمري في مادة طرائق التدريس.